(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
India is a place that is known for decent varieties and has given the Indian novelists assortment of subjects like a variegated and pleasant situation of the contentions and conflicts of different networks keeping distinctive religions, deciphering society in various ways and experiencing immense and significant changes attributable to new arrangement of education and learning. The elements of the contemporary religious, educational and social advancement and in addition her conventional convictions and traditions get an abundant articulation in the novels of Indian English Fiction. In the contemporary society, Indian English Novelists confront the new issue of giving aesthetic articulation the cutting edge man, alongside the hardest assignment of uncovering the unending issues of Indian idea, convictions and culture, his state of mind towards Western education and its effect on his philosophy of life.